2015
DOI: 10.1186/s13075-015-0561-1
|View full text |Cite
|
Sign up to set email alerts
|

Polychromatic flow cytometry in evaluating rheumatic disease patients

Abstract: B cells are central players in multiple autoimmune rheumatic diseases as a result of the imbalance between pathogenic and protective B-cell functions, which are presumably mediated by distinct populations. Yet the functional role of different B-cell populations and the contribution of specific subsets to disease pathogenesis remain to be fully understood owing to a large extent to the use of pauci-color flow cytometry. Despite its limitations, this approach has been instrumental in providing a global picture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 101 publications
(135 reference statements)
1
13
0
Order By: Relevance
“…The subset of NSM B-cells has been implicated in immune responses against T-cell independent antigens, however recent studies confirmed their role as a long-lasting memory to T-cell dependent antigens involved in reconstitution of switched memory pool upon antigen restimulation [10]. Changes in NSM fraction were accompanied by increased percentage of immature/ /early-transitional B-cells and activated SM cells, both [8,16,23]. Nevertheless, systemic accumulation of B-cells with CD27+CD21 low phenotype, e.g.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The subset of NSM B-cells has been implicated in immune responses against T-cell independent antigens, however recent studies confirmed their role as a long-lasting memory to T-cell dependent antigens involved in reconstitution of switched memory pool upon antigen restimulation [10]. Changes in NSM fraction were accompanied by increased percentage of immature/ /early-transitional B-cells and activated SM cells, both [8,16,23]. Nevertheless, systemic accumulation of B-cells with CD27+CD21 low phenotype, e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Samples were fixed with FACS lysing solution (BD Biosciences), washed and analyzed in FACS Canto II flow cytometer (BD Biosciences). Based on differential expression of surface markers the following B-cell subsets were identified: immature/ /early-transitional (I/T, CD27-IgD+CD21 low ), late-transitional/naïve (CD27-IgD+CD21+), non-switched memory (NSM, CD27+IgD+), resting class-switched memory (SM, CD27+IgD-CD21+), activated SM (CD27+IgD-CD21 low ), and double-negative (CD27-IgD-) exhausted memory (ExM) as summarized in Figure 1C [8,16,23,25]. Using T-cell panel we identified four subsets within CD4+ or CD8+ gate: naïve (CD45RA+CD45RO-CCR7+), central memory (T CM , CD45RA-CD45RO+CCR7+), effector memory (T EM , CD45RA-CD45RO+CCR7-), and effector memory CD45RA+ (T EMRA , CD45RA+CD45RO-CCR7-) [26,27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a typical sequence of events, PBMC are analyzed using multidimensional flow cytometry after staining for 12–16 surface and intracellular markers. This approach identifies quantitative abnormalities of B-cell homeostasis between SLE, HC, and other autoimmune diseases (25, 26, 29, 30). Moreover, through the use of an increasing number of agnostic automated analytical methods (31, 32), cytometry analysis has the power to identify unheralded populations characteristic of different disease conditions.…”
Section: Integrating Repertoire Analysis Into a B-cell Immunomics Appmentioning
confidence: 99%
“…27,28 Addressing these questions requires a comprehensive experi- HC, and other autoimmune diseases. 25,26,29,30 Moreover, through the use of an increasing number of agnostic automated analytical methods, 31,32 cytometry analysis has the power to identify unheralded populations characteristic of different disease conditions. Similar multidimensional datasets can be obtained through other cytometry methods including CyTOF and Chip-Cytometry.…”
Section: Integ R Ating Repertoire Analys Is Into a B-cell Immunomi mentioning
confidence: 99%